A High‐Throughput Screening Assay to Identify Kidney Toxic Compounds. Issue 1 (6th August 2018) - Ramm, Susanne; Adler, Melanie; Vaidya, Vishal S.
Abstract: Kidney toxicity due to drugs and chemicals poses a significant health burden for patients and a financial risk for pharmaceutical companies. However, currently no sensitive and high‐throughput in vitro method exists for predictive nephrotoxicity assessment. Primary human proximal tubular epithelial cells (HPTECs) possess characteristics of differentiated epithelial cells, making them a desirable model to use in in vitro screening systems. Additionally, heme oxygenase 1 (HO‐1) protein expression is upregulated as a protective mechanism during kidney toxicant‐induced oxidative stress or inflammation in HPTECs and can therefore be used as a biomarker for nephrotoxicity. In this article, we describe two different methods to screen for HO‐1 increase: A homogeneous time resolved fluorescence (HTRF) assay and an immunofluorescence assay. The latter provides lower throughput but higher sensitivity due to the combination of two readouts, HO‐1 intensity and cell number. The methods described in the protocol are amendable for other cell types as well. © 2016 by John Wiley & Sons, Inc.